pdf
keyboard_arrow_up
School
The Chinese University of Hong Kong *
*We aren’t endorsed by this school
Course
3230
Subject
Mathematics
Date
Nov 24, 2024
Type
Pages
5
Uploaded by MinisterGorilla8297
MATH3230 Numerical Analysis
Tutorial 4
1
Recall:
Quasi-Newton method:
We first consider Newton’s method:
x
k
+1
=
x
k
−
f
(
x
k
)
f
′
(
x
k
)
,
k
= 0
,
1
,
2
,
. . . .
(1)
At each iteration, we need to compute
f
′
(
x
k
)
. This might be very difficult to do in some cases. For instance:
(
a
)
the expression
f
(
x
)
is unknown;
(
b
)
the derivative
f
′
(
x
)
is very expensive to compute;
(
c
)
the value of function
f
may
be the result of a long numerical calculation, so the derivative has no formula available.
1.
Constant slope method:
Approximating
f
′
(
x
k
)
by a constant
g
k
=
g
, Newton’s method becomes
x
k
+1
=
x
k
−
f
(
x
k
)
g
,
k
= 0
,
1
,
2
,
. . . .
(2)
This is called the constant slope method. In particular, we might take
g
=
f
′
(
x
0
)
.
2.
Secant method:
Approximating
f
′
(
x
k
)
by
g
k
=
f
(
x
k
)
−
f
(
x
k
−
1
)
x
k
−
x
k
−
1
,
Newton’s method becomes
x
k
+1
=
x
k
−
f
(
x
k
)
g
k
,
k
= 0
,
1
,
2
,
. . . .
(3)
This is called the secant method. Two initial values
x
0
and
x
1
are needed to start.
3.
Fixed-point iterative methods:
Both Newton’s method and Quasi-Newton’s method can be seen as special cases
of fixed-point iterative methods. For a given function
φ
(
x
)
,
x
∗
is called its fixed point if
x
∗
satisfies
φ
(
x
∗
) =
x
∗
.
The iterative method
x
k
+1
=
φ
(
x
k
)
,
k
= 0
,
1
,
2
, . . .
is called a fixed-point iterative method associated with the function
φ
(
x
)
, and
φ
(
x
)
is called the iterative function.
Theorem 1
(Convergence of fixed-point iterative method)
.
If the iterative function
φ
(
x
)
satisfies the condition
|
φ
′
(
x
∗
)
|
<
1
,
then there exists
δ >
0
such that for any
x
0
∈
[
x
∗
−
δ, x
∗
+
δ
]
, the fixed-point iterative method converges. If
φ
′
(
x
∗
)
̸
= 0
,
the convergence is linear with convergence rate
ρ
=
|
φ
′
(
x
∗
)
|
. If
φ
′
(
x
∗
) =
φ
′′
(
x
∗
) =
· · ·
=
φ
(
p
−
1)
(
x
∗
) = 0
,
but
φ
(
p
)
̸
= 0
,
then the fixed-point iterative method converges with order
p
.
4.
Cases with multiple zeros:
A point
x
∗
is called a zero of the function
f
(
x
)
with multiplicity
m
≥
1
if it holds
f
(
x
∗
) =
f
′
(
x
∗
) =
· · ·
=
f
(
m
−
1)
(
x
∗
) = 0
, but
f
(
m
)
(
x
∗
)
̸
= 0
.
5.
Convergence of Newton’s method in the case of multiplicity:
We have the following local convergence of
Newton’s method when it is applied for solving a nonlinear equation with a zero of multiplicity
m
:
(a) It converges quadratically for
m
= 1
, namely when
x
∗
is a single zero;
(b) It converges only linearly to the multiple zero
x
∗
with rate
ρ
= 1
−
1
m
for
m >
1
. If
m
= 2
, the convergence rate
is
1
/
2
, the same as the convergence rate of the bisection algorithm. Newton’s method converges more slowly
when
m
is larger.
1
2
Exercises:
Please do the star problem (*) in tutorial class and finish the rest after class.
1. * Consider the following nonlinear equation
f
(
x
) :=
x
3
−
2
x
2
+
x
= 0
,
and the sequence generated from an iterative function
ϕ
:
R
→
R
such that
x
n
+1
=
ϕ
(
x
n
)
with initial guess
x
0
.
(a) For the iterative function
ϕ
(
x
) :=
x
−
2
f
(
x
)
f
′
(
x
)
.
Does the fixed-point iterative method have local convergence near
x
= 1
? If so, find the order of convergence.
(b) For the iterative function
ϕ
(
x
) :=
x
+ 10
f
(
x
)
f
′
(
x
)
.
Does the fixed-point iterative method have local convergence near
x
= 1
? If so, find the order of convergence.
(c) Which iterative function
ϕ
(
x
)
(the one in (a) and (b)) is better for the fixed-point iterative method? Please
explain.
Solution.
Note that
f
=
x
(
x
−
1)
2
,
f
′
= (
x
−
1)(3
x
−
1)
,
f
′′
= 6
x
−
4
,
f
′′′
= 6
.
(a) Consider
ϕ
′
(
x
)
=
1
−
2
[
f
′
(
x
)]
2
−
f
′′
(
x
)
f
(
x
)
[
f
′
(
x
)]
2
=
−
1 +
2
f
′′
(
x
)
f
(
x
)
(
f
′
(
x
))
2
=
−
1 +
2
x
(
x
−
1)
2
(6
x
−
4)
(
x
−
1)
2
(3
x
−
1)
2
=
−
1 +
4
x
(3
x
−
2)
(3
x
−
1)
2
.
Hence, we have
ϕ
′
(1) = 0
.
Also, notice that
ϕ
′′
(
x
)
=
4
(3
x
−
1)
4
(
2(3
x
−
1)
3
−
6(3
x
−
1)(3
x
−
2)
x
)
=
8
(3
x
−
1)
3
.
Hence,
ϕ
′′
(1)
̸
= 0
.
We conclude that the fixed-point iterative method has convergence of order
2
.
(b) Note that
ϕ
′
(
x
)
=
1 + 10
[
f
′
(
x
)]
2
−
f
′′
(
x
)
f
(
x
)
[
f
′
(
x
)]
2
= 11
−
10
f
′′
(
x
)
f
(
x
)
(
f
′
(
x
))
2
=
11
−
10
2
x
(3
x
−
2)
(3
x
−
1)
2
.
Because
ϕ
′
(1) = 11
−
5 = 6
>
1
. this iteration can not ensure local convergence near
x
= 1
.
(c) The one in
(
a
)
is better, as the corresponding fixed-point iterative method converges with order 2.
2
2.
(a) * Write down the general form for a fixed-point iterative method. Point out why Newton’s and quasi-Newton’s
methods are special cases of the fixed-point iterative method.
(b) Let
{
x
n
}
be the sequence generated from the fixed-iterative method and
ϕ
(
x
)
be the iterative function. Under
proper choice of
x
0
and conditions on
ϕ
x
, prove that
x
n
converges to
x
∗
where
ϕ
(
x
∗
) =
x
∗
, please specify all
assumption you need on
ϕ
and
x
0
clearly.
Solution.
(a) A fixed-point iterative method is
x
n
+1
=
ϕ
(
x
n
)
.
For Newton’s method,
ϕ
(
x
n
) =
x
n
−
f
(
x
n
)
f
′
(
x
n
)
; for quasi Newton’s method,
ϕ
(
x
n
) =
x
n
−
f
(
x
n
)
g
n
where
g
n
is an
approximation to
f
′
(
x
n
)
.
(b) Assume that
|
φ
′
(
x
∗
)
|
<
1
.
Then
x
k
+1
−
x
∗
=
φ
(
x
k
)
−
φ
(
x
∗
) =
φ
′
(
ξ
k
)(
x
k
−
x
∗
)
,
where
ξ
k
lies between
x
k
and
x
∗
. As
|
φ
′
(
x
∗
)
|
<
1
.
, there exists an
δ >
0
such that
|
φ
′
(
x
)
| ≤
α <
1
∀
x
∈
[
x
∗
−
δ, x
∗
+
δ
]
.
Then we can see that
{
x
k
}
will lie inside the interval
[
x
∗
−
δ, x
∗
+
δ
]
as long as the initial guess
x
0
∈
[
x
∗
−
δ, x
∗
+
δ
]
.
This implies
|
x
k
+1
−
x
∗
|
=
|
φ
′
(
ξ
k
)
||
(
x
k
−
x
∗
)
| ≤
α
|
x
k
−
x
∗
|
,
or
|
x
k
+1
−
x
∗
| ≤
α
k
+1
|
x
0
−
x
∗
|
.
Thus we know
x
k
→
x
∗
as
k
→ ∞
, or the fixed-point iterative method converges locally.
3. Note that the fixed-point theorem is a special case of the general contraction mapping theorem.
Let
C
⊂
R
be an closed interval and
F
:
C
→
C
. We say that
F
is a contractive mapping on
C
if there exists
s
,
0
< s <
1
such that
|
F
(
x
)
−
F
(
y
)
| ≤
s
|
x
−
y
|
for all
x, y
∈
C
. Then if
F
is a contractive mapping ,
F
has a unique
fixed point in
C
and any sequence generated from
x
n
+1
=
F
(
x
n
)
with
x
0
in
C
converges.
(a) Show that if a function
F
is continuous and differentiable in
C
, and
|
F
′
(
x
)
|
<
1
, then
F
will be a contractive
mapping in
C
⊂
R
.
(b) Using the contractive mapping theorem, show the sequence generated from
x
n
+1
= 3
−
1
2
|
x
n
|
,
x
0
=
−
15
,
converges.
Solution.
(a) By mean value theorem, for
∀
x, y
∈
C
, there is some
ξ
∈
C
, such that
|
F
(
x
)
−
F
(
y
)
|
=
|
F
′
(
ξ
)
| · |
x
−
y
|
.
Since
C
is closed, the maximum of
|
F
′
(
x
)
|
is obtained at some point
x
0
. So
|
F
′
(
x
)
|
⩽
max
|
F
′
(
x
)
|
=
|
F
′
(
x
0
)
|
<
1
.
Thus
F
is a contractive mapping in
C
.
(b) Let
F
(
x
) = 3
−
1
/
2
|
x
|
, then we have
|
F
(
x
)
−
F
(
y
)
|
=
|
3
−
1
/
2
|
x
| −
3 + 1
/
2
|
y
||
=
1
2
||
x
| − |
y
|| ≤
1
2
|
y
−
x
|
.
This shows
F
(
x
)
is a contractive mapping and so
x
n
converges.
4. Consider using the secant method to solve
f
(
x
) = 0
where
f
(
x
)
is a smooth nonlinear function with initial guess
x
0
and
x
1
. Let
{
x
n
}
be the sequence generated from the secant method.
3
Your preview ends here
Eager to read complete document? Join bartleby learn and gain access to the full version
- Access to all documents
- Unlimited textbook solutions
- 24/7 expert homework help
(a) * Let
f
(
x
) =
x
2
−
3
x
+ 1
and
x
0
= 1
,
x
1
= 3
, compute
x
3
generated from the secant method.
(b) Show that if
f
′
(
q
)
̸
= 0
and
x
n
→
q
as
n
→ ∞
, then
f
(
q
) = 0
.
Solution.
(a) By secant method, we have
f
(
x
1
) = 1
,
f
(
x
0
) =
−
1
,
x
2
=
f
(
x
1
)
x
0
−
x
1
f
(
x
0
)
f
(
x
1
)
−
f
(
x
0
)
=
3 + 1
2
= 2
,
f
(
x
2
) =
−
1
,
f
(
x
1
) = 1
,
x
3
=
f
(
x
2
)
x
1
−
x
2
f
(
x
1
)
f
(
x
2
)
−
f
(
x
1
)
=
−
3
−
2
−
2
= 2
.
5
.
(b) By secant method, we have
x
n
+1
=
x
n
−
f
(
x
n
)
x
n
−
x
n
−
1
f
(
x
n
)
−
f
(
x
n
−
1
)
.
We notice that if
x
n
→
q
, we have
f
(
x
n
) =
f
(
q
) +
f
′
(
q
)(
x
n
−
q
) +
f
′′
(
ζ
n
)(
x
n
−
q
)
2
. Hence
lim
n
→∞
x
n
−
x
n
−
1
f
(
x
n
)
−
f
(
x
n
−
1
)
=
1
f
′
(
q
)
.
Therefore,
q
=
q
−
f
(
q
)
/f
′
(
q
)
which implies
f
(
q
) = 0
.
5. Let
x
∗
be a root of
f
(
x
)
with multiplicity
2
and
f
(
x
)
is continuous and differentiable up to the second order near
x
∗
.
(a) * Let
φ
(
x
) =
x
−
a
f
(
x
)
f
′
(
x
)
,
0
< a
≤
2
.
Show that
lim
x
→
x
∗
φ
′
(
x
) = 1
−
a
2
.
(b) * Let
x
n
+1
=
x
n
−
a
f
(
x
n
)
f
′
(
x
n
)
,
0
< a
≤
2
,
Show
{
x
n
}
converges in a neighborhood of
x
∗
.
(c) For the sequence generated from (b), let
ϵ
n
=
x
n
−
x
∗
. Assuming there exist
δ >
0
, such that
φ
′′
(
x
)
is bounded
when
|
x
−
x
∗
|
< δ
. Prove that, when
a
= 2
,
|
ϵ
n
+1
|
< Cϵ
2
n
,
for some positive constant
C
.
(d) Apply the iteration in (b) with
a
= 2
to find the root of
f
(
x
) =
x
5
−
3
x
4
−
18
x
3
+ 86
x
2
−
111
x
+ 45
with initial value
x
0
=
2.5, please write down the approximate solution at the
4
th
iteration .
Solution.
(a) We note that by definition of
φ
, we have
lim
x
→
x
∗
φ
′
(
x
) = 1
−
a
+
a
lim
x
→
x
∗
f
(
x
)
f
′′
(
x
)
f
′
(
x
)
2
.
Since
x
∗
is a root of
f
(
x
)
with multiplicity
2
, then
f
(
x
)
can be written as
f
(
x
) = (
x
−
x
∗
)
2
g
(
x
)
, where
g
(
x
)
is
two times continuously differentiable and
g
(
x
∗
)
̸
= 0
.
Therefore, we have
f
′
(
x
)
=
2(
x
−
x
∗
)
g
(
x
) + (
x
−
x
∗
)
2
g
′
(
x
)
,
f
′′
(
x
)
=
2
g
(
x
) + 4(
x
−
x
∗
)
g
′
(
x
) + (
x
−
x
∗
)
2
g
′′
(
x
) ;
4
which implies
lim
x
→
x
∗
f
(
x
)
f
′′
(
x
)
f
′
(
x
)
2
=
lim
x
→
x
∗
(
x
−
x
∗
)
2
g
(
x
)(2
g
(
x
) + 4(
x
−
x
∗
)
g
′
(
x
) + (
x
−
x
∗
)
2
g
′′
(
x
))
(2(
x
−
x
∗
)
g
(
x
) + (
x
−
x
∗
)
2
g
′
(
x
))
2
=
lim
x
→
x
∗
2
g
2
(
x
) + 4(
x
−
x
∗
)
g
(
x
)
g
′
(
x
) + (
x
−
x
∗
)
2
g
(
x
)
g
′′
(
x
)
4
g
2
(
x
) + 4(
x
−
x
∗
)
g
(
x
)
g
′
(
x
) + (
x
−
x
∗
)
2
g
′
(
x
)
2
=
1
2
.
Hence,
lim
x
→
x
∗
ϕ
′
(
x
) = 1
−
a/
2
.
(b) Since
0
⩽
φ
′
(
x
∗
) = 1
−
a
2
<
1
, there exists a (closed) neighbourhood of
x
∗
, say
B
(
x
∗
, δ
)
such that
0
⩽
φ
′
(
x
)
⩽
c <
1
, for
∀
x
∈
B
(
x
∗
, δ
)
. Note that
φ
(
x
∗
) =
x
∗
as
f
(
x
∗
) = 0
. Define
ϵ
n
+1
=
x
n
+1
−
x
∗
=
φ
(
x
n
)
−
φ
(
x
∗
)
, then
by mean value theorem,
ϵ
n
satisfies:
ϵ
n
+1
=
φ
′
(
ζ
n
)(
x
n
−
x
∗
) =
φ
′
(
ζ
n
)
e
n
where
ζ
n
lies between
x
n
and
x
∗
. Therefore, we have
ϵ
n
→
0
as
c <
1
.
(c) We note that the Taylor series of
ϕ
(
x
∗
+
ϵ
n
)
is
x
n
+1
=
φ
(
x
n
) =
φ
(
x
∗
) +
φ
′
(
x
∗
)(
x
n
−
x
∗
) +
φ
′′
(
ξ
)
2
(
x
n
−
x
∗
)
2
,
where
ξ
lies between
x
∗
and
x
n
. If
a
= 2
, we have
φ
′
(
x
∗
) = 1
−
a
2
= 0
. Moreover, since
φ
(
x
∗
) =
x
∗
, we have
|
ϵ
n
+1
|
=
|
x
n
+1
−
x
∗
|
=
|
φ
′′
(
ξ
)
|
2
ϵ
2
n
< Cϵ
2
n
.
Here we use the assumption that
φ
′′
(
ξ
)
2
is bounded in the neighborhood of
x
∗
.
(d) We note
f
′
(
x
) = 5
x
4
−
12
x
3
−
54
x
2
+ 172
x
−
111
, then the iteration is
x
k
+1
=
x
k
−
2
x
5
−
3
x
4
−
18
x
3
+ 86
x
2
−
111
x
+ 45
5
x
4
−
12
x
3
−
54
x
2
+ 172
x
−
111
The results of the first four iterations are as follows:
x
0
=
2
.
5
x
1
=
3
.
2895
x
2
=
3
.
036414485
x
3
=
3
.
000719162
.
5